Major adverse cardiac events in vascular surgery patients with peripheral arterial disease: Major advers cardiac events in PAD patients - Dabic, Petar; Petrović, Jovan; Vucurevic, Bojan; Sevkovic, Milorad; Pesic, Slobodan; Neskovic, Mihailo; Tanaskovic, Slobodan; Gajin, Predrag; Ilijevski, Nenad (Medical Research, 2024)
Introduction: Major adverse cardiac events (MACE) are the primary cause of morbidity and mortality in patients undergoing vascular surgical procedures. Because of this it is essential to understand the relationship between coronary artery disease and peripheral arterial disease. In this paper, we aimed to determine predictors and risk factors related to the occurrence of MACE in patients undergoing vascular surgery for peripheral arterial disease. Material and Methods: This is a retrospective study of 310 in hospital patients treated at a high-volume vascular centre. Outcome was classified through the three-point MACE (myocardial infarction, stroke and cardiovascular mortality). Results: We found that majority of initial MACE happened in patients with aortobifemoral bypass surgery compared to other types of reconstructions (p=0.009). No significant correlation was established between the procedures performed and the short-term primary outcome. In the initial period, MACE was detected in 14 (5.8%) patients. Among them, six (1.9%) experienced a myocardial infarction (MI), three (1%) had a stroke, and five (1.6%) died within the first 30 days. All deaths were linked to cardiac ischemia, which ultimately culminated in cardiogenic shock and subsequent death. Short term MACE was observed for 2 (0.6%) patients both of whom had a MI. Conclusion: Major vascular surgery in patients with coronary artery disease is a highly morbid procedure and perioperative MACE places them at significantly high risk of mortality. Early detection of coronary heart disease and preoperative optimization can play a major role in reducing the risk of MACE.